Experimental and Computational Thermodynamic Study of Three Monofluoronitrobenzene Isomers - da Silva, MAVR (2010)
The present work reports the thermodynamic study performed on three monofluorinated nitrobenzene derivatives by a combination of experimental techniques and computational approaches. The standard (p degrees = 0.1 MPa) molar enthalpies of formation in the liquid phase of the three isomers of fluoronitrobenzene were derived from the standard molar energies of combustion, in oxygen, at T = 298.15 K, measured by rotating bomb combustion calorimetry. The vapor pressure study of the referred compounds was done by a static method and, from the obtained results, the phase diagrams were elaborated, and the respective triple point coordinates, as well as the standard molar enthalpies of vaporization, sublimation and fusion, at T = 298.15 K, were determined. The combination of some of the referred thermodynamic parameters yielded the standard (p degrees = 0.1 MPa) molar enthalpies of formation in the gaseous phase, at T = 298.15 K, of the studied compounds: Delta(f)H(m)degrees(2-fluoronitrobenzene, g) = -(102.4 +/- 1.5) kJ.mol(-1), Delta(f)H(m)degrees(3-fluoronitrobenzene, g) = -(128.0 +/- 1.7) kJ.mol(-1), and Delta(f)H(m)degrees(4-fluoronitrobenzene, g) = -(133.9 +/- 1.4) kJ.mol(-1). Using the empirical scheme developed by Cox, values of standard molar enthalpies of formation in the gaseous phase were estimated and afterwards compared with the ones obtained experimentally, and both were interpreted in terms of the molecular structure of the compounds. The theoretically estimated gas-phase enthalpies of formation were calculated from high-level ab initio molecular orbital calculations at the G3(MP2)//B3LYP level of theory. The computed values compare very well with the experimental results obtained in this work and show that 4-fluoronitrobenzene is the most stable isomer from the thermodynamic point of view. Furthermore, this composite approach was also used to obtain information about the gas-phase basicities, proton and electron affinities and, finally, adiabatic ionization enthalpies.